SHARPSports mental Health Awareness Research Project: Prevalence and risk factors of depressive symptoms and life stress in elite athletes. Issue 12 (December 2017) - Beable, Sarah; Fulcher, Mark; Lee, Arier C.; Hamilton, Bruce
Abstract: Objectives: Our study aims to estimate the prevalence of symptoms of depression and daily life hassles in elite athletes. Design: A cross-sectional prospective epidemiological study design. Methods: An online anonymous survey was administered during a 2-month period from May to July 2015. Athletes 18 years of age (or older) who were members of the High Performance Sport New Zealand programme were invited to participate. Of 370 potential participants, 187 completed responses were received (51%). Symptoms of depression were measured by the Centre for Epidemiological Studies Depression Scale—Revised (CESD-R). Life stress was measured by the Daily Hassles Questionnaire. Results: Overall 21% (n = 39) of participants reported symptoms consistent with depression. Only 2 of the 39 athletes were currently taking an anti-depressant medication. Those contemplating retirement, partaking in individual sport, and who were less than 25 years old had significantly increased odds of experiencing depression. Reported life stressors were higher in females, in those who play an individual sport and those in a centralised programme. There was a significant correlation between higher levels of life stress and experiencing depressive symptoms. Conclusions: This study highlights that depressive symptoms are prevalent in elite athletes with multiple potential risk factors identified including high life stress. These variables warrant further exploration to enable the early identification of athletes with depressive symptoms, screening and support for elite athletes.